2017
DOI: 10.18203/2394-6040.ijcmph20170300
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and implications of HIV prevention programme among uniform service personnel: a systematic evaluation of HAF II project in Kogi state, Nigeria

Abstract: Background: Considering HIV pandemic among uniform service personnel (UPS), a lot of HIV intervention programmes designed to mitigate the spread have not been very successful thus the introduction of the HIV minimum prevention package intervention (MPPI). This paper therefore presents the achievements of HIV prevention programme among UPS in Kogi State, Nigeria including its implications for programming. Methods: This project was implemented among uniform service personnel who are in army, police, custom and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
2
2
2
Order By: Relevance
“…As more community dialogue sessions were held, more community influencers who were the participants were trained. This result is consistent with the findings of a similar study carried out among outof-school youths in Nigeria (Adelekan et al, 2017). Community entry and advocacy which are important component of the structural intervention is important to ensure acceptance and ownership of a programme.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As more community dialogue sessions were held, more community influencers who were the participants were trained. This result is consistent with the findings of a similar study carried out among outof-school youths in Nigeria (Adelekan et al, 2017). Community entry and advocacy which are important component of the structural intervention is important to ensure acceptance and ownership of a programme.…”
Section: Discussionsupporting
confidence: 91%
“…Biomedical intervention in this project included HIV counselling and testing, and condom uptake. From this project, less proportion of people had the HCT done in the year 2015 compared to the preceding year, this finding is inconsistent with the previous study (Adelekan et al, 2017). Responses from the civil society organisations during the in-depth interview sessions revealed that this might be due to some periods of unavailability of test kits, this is a major shortfall as some out-of-school youths might be missed during this period.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, our findings were much lower than 43% that was reported in a nationwide survey among Thai uniformed personnel. The differences in findings could be due to the fact that most new recruits are likely to be single or have non-regular partners, less inclined to abstinence and more likely to engage in transactional sex [22].…”
Section: Discussionmentioning
confidence: 95%
“…However, our ndings were much lower than 43% that was reported in a nationwide survey among Thai uniformed personnel. The differences in ndings could be due to the fact that most new recruits are likely to be single or have non-regular partners, less inclined to abstinence and more likely to engage in transactional sex [22].…”
Section: Discussionmentioning
confidence: 99%